Evidence from systematic reviews on policy approaches to improving access to medicines - Celestino Kuchena; Abubaker Qutieshat (PAGEPress Publications, 2023)
The prevailing frameworks on access to medicines advise global procurement as a solution by assuming the presence of medicines on the global market. Yet access to medicines remains challenging, especially in developing countries. This is a global worry because the UN considers limited access to essential medicines as one of the five indicators of securing the right to health. To fill a research gap in health system studies and inform policymaking, we synthesized evidence from systematic reviews of how government policies affect low- and middle-income country (LMIC) medicine access. We chose a rapid review approach to reduce timelines and avoid missing policy "windows of opportunity." To include only studies published after the start of COVID-19, we chose systematic reviews published between 2019 and November 2nd, 2022. This was also in line with recommendations in the literature to look at recent systematic reviews. The themes were grouped using a thematic and textual narrative approach. This review included 32 studies that examined access to medicine from various perspectives. Both supply- and demand-side policies are needed to improve medical access. LMICs cannot afford medicines, and supply never meets demand. LMICs will continue to struggle with pharmaceutical pricing due to their limited bargaining power. The urban bias in health facilities and policy changes reduce medicine availability and use. Leaders must make policy decisions to sustain domestic funds. Policymakers should consider that organizations may act against policy goals. Instead of copying developed nations, LMIC governments must develop multipronged strategies to address their unique challenges.